A New Sponin From the Leaves of Streblus Asper - Chaturvedi, S.K. (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the leaves of streblus asper have resulted in the isolation and identification of a new saponin-3-O-acetyl olean-12-ene-28-oic-O-b-D-gluco pyranosyl-(1-4)-O-b-D-xylo pyranoside.